Impact of management’s irrational expectations on corporate tax avoidance: A mediating effect based on level of risk-taking - Li, Lingyu; Wu, Qing (Frontiers in Psychology, 2022)
Frequent tax avoidance incidents have caused huge losses to corporate reputation and corporate value. Research is required on whether and how the irrational judgment of management, a powerful factor in corporate decision-making, affects corporate tax avoidance behavior. Taking all A-share listed companies from 2006 to 2020 as a sample, this paper empirically tests the relationships among management’s irrational expectations, level of corporate risk-taking, and level of corporate tax avoidance using an fixed effects regression model (FEM). The results of the three-stage regression model and Sobel test suggest that the level of corporate risk-taking plays a mediating role between managers’ irrational expectations and Corporate tax avoidance. The managers’ stockholding plays a moderating role in this process. This study also finds evidence that the irrational expectations of management lead to an increase in levels of research and development manipulation, which indirectly increases the level of corporate tax avoidance. Therefore, to control the risk caused by managers’ risky decisions, such as R&D manipulation and tax avoidance, it is necessary to lessen the effects of irrational expectations of management, and the management equity incentive plan has been identified as a reliable method in the risk reduction process.